Business Combinations and Accounting Valuation - Parker, William M. (Journal of Accounting Research, 1966)
On the occasion of a corporate merger or combination, the most important issue which arises is the restatement of assets from historical costs to current values. Whether to make such an adjustment is the primary decision to be made before any other major question is considered.' Thus far, the usual approach to this problem has been to base the decision upon whether the combination qualifies as a or a of interests. The first expression refers to situations in which assets of certain parties to the transaction are deemed, in effect, to have been purchased by the surviving entity or interests, with the implied conclusion that they should be restated to current market figures. In the second case, assets are conceived as being merged, without any inference of a transfer or thereof. The implication in this latter case is, of course, that the merged assets should retain the bases of accountability previously adopted by the constituent firms, and this normally means unamortized historical costs. Thus, the attention of accountants has been given primarily to the development of rational criteria for distinguishing between the purchase and the pooling situation, as those two terms have been defined. The continuity of individual stock ownership, management, business objectives, and the business enterprise have all been postulated as appropriate guidelines, together with such other considerations as the relative sizes